Sex-specific associations of the controlling nutritional status score with diabetic kidney disease among Chinese individuals: a retrospective cross-sectional study - Han, Yu-Nan; Wang, Tong; Lin, Qin; Li, Lin; Ren, Yan-Rui (Frontiers in Nutrition, 2025)
BackgroundRecognizing the crucial role of nutritional status in the advancement of diabetic complications, this investigation aimed to evaluate sex-specific disparities concerning the relationship between the Controlling Nutritional Status (CONUT) score and diabetic kidney disease (DKD).MethodsData obtained from the First Affiliated Hospital of Yangtze University, spanning January 2022 to May 2024, were utilized. The CONUT score was determined utilizing serum albumin (ALB), total cholesterol (TC), and lymphocyte (LYM) count. Sex-specific correlations among CONUT scores and DKD were evaluated using multivariate logistic regression and restricted cubic splines (RCS). Receiver operating characteristic (ROC) curve analysis was employed to ascertain the area under the curve (AUC) for the CONUT score in female participants. Subgroup analyses and interaction assessments were conducted to investigate the influence of the CONUT score within sex-specific subgroups.ResultsA total of 1,429 individuals were enrolled. Following adjustment for all covariates, women within the elevated CONUT score group exhibited a 66% augmented odds of DKD [OR = 1.66 (95%CI: 1.08–2.58)]. RCS analysis indicated a linear positive correlation between the CONUT score and the odds of DKD in women (P-non-linear: 0.840). The AUC for the CONUT score in women was 0.700 (95%CI: 0.653–0.748), indicating its potential utility as a risk identification tool for DKD. Subgroup analyses revealed a noteworthy positive correlation between elevated CONUT scores and the odds of DKD among females aged ≥60 years, those with a high school diploma, who smoked, consumed alcohol, were not hypertensive, had hyperlipidemia, or had a high TC/HDL ratio.ConclusionThis study demonstrates sex-specific disparities in the prevalence of DKD associated with elevated CONUT scores. These outcomes underscore the significance of individualized nutritional interventions for females at an elevated odd of DKD.